China's formal online education under COVID-19 : actions from government, schools, enterprises and families - Zhan, Zehui, 1983-; Huo, Liming, 1996-; Yao, Xiao, 1995-; Zhong, Baichang, 1978- (London: Routledge, 2022)
'This book investigates how schools, enterprises and families in China have coped with the formal online education in the light of government policy throughout the COVID-19 epidemic outbreak, with special focus on the problems they have encountered and possible solutions. Using grounded theory, over 1000 posts retrieved from public online forums were analyzed under a 4*4 framework, referring to four special time nodes (proposal period, exploratory period, full deployed period, exiting period) and four major subjects (government, schools, enterprises, families). The book identifies four main issues faced by massive online education during the epidemic: platform selection in proposal period, teacher training in exploratory period, resource integration in full deployed period, and flexibility of returning to schools in exiting period. These findings enlighten us with a deeper understanding of the process of online learning in an educational emergency, helping to develop best countermeasures in similar situations, as well as to provide paths to follow for other countries. The book will appeal to teachers, researchers and school administrators of the online education and education emergency management, as well as those who are interested in Chinese education during the COVID-19 outbreak in general'--
Introduction -- Theoretical basis -- Research method -- The first stage: Proposal period -- The second stage: Exploratory period -- The third stage: Full deployed period -- The fourth stage: Exiting period -- Discussions -- Implication.
Includes bibliographical references and index.
Keywords: Web-based instruction -- China; COVID-19 Pandemic, 2020- -- China; Social distancing (Public health) and education -- China; Education and state -- China; Educational change -- China; Teachers -- Training of -- China